Omissão e colocação de clíticos por crianças bilingues Português-Francês - Tomaz, Margarida; Lobo, Maria; Madeira, Ana; Soares-Jesel, Carla; Vaz, Stéphanie (Revista da Associação Portuguesa de Linguística, 2019)
This study investigates clitic omission and clitic placement in Portuguese-French bilingual children. Using two elicited production tasks, we show that the global pattern of development is very similar to the one found in monolingual acquisition: bilingual children are sensitive to the type of clitic (more omission in accusative contexts than in reflexive contexts), syntactic context (higher rates of pronoun production in islands than in simple sentences), and animacy (the rates of omission are always higher with inanimate antecedents). As for clitic placement, although the developmental path is similar to monolinguals, we find higher rates of proclisis in the bilinguals both in enclitic and in proclitic contexts, which may be caused by language transfer from French, although there are individual differences. We also show that a smaller group of Portuguese-French bilingual children who are speakers of the Brazilian Portuguese variety and exposed to European Portuguese in school context (and who are thus not only bilingual, but also bilectal) differ from the European PortugueseFrench bilinguals both in the rates of clitic production and in clitic placement patterns.